2004
DOI: 10.1111/j.1475-6803.2004.t01-1-00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Demand Curves for Small Stocks Slope Down?

Abstract: Stocks added to the S&P 500 generally experience positive abnormal returns following the announcement. Several competing explanations exist for this reaction, but small sample sizes and other issues make it difficult to distinguish among them. We examine this subject using the small-cap Russell 2000 index, which has several advantages over the S&P 500 in this context. Our primary finding is that stocks added to or deleted from the Russell 2000 experience significant changes in stock price and trading volume, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 22 publications
8
57
2
Order By: Relevance
“…This consideration should be especially relevant to relatively concentrated indices such as the JSE Top 40 and the SWIX 40. 3 Mase (2007) makes a similar argument for the FTSE100, and confirms this by demonstrating that for the FTSE100 the index migration price effects are similar for first-time and returning index constituents. Unfortunately there are not yet enough instances of index re-entries on the JSE to make a similar analysis meaningful.…”
Section: Prior Literaturementioning
confidence: 74%
See 2 more Smart Citations
“…This consideration should be especially relevant to relatively concentrated indices such as the JSE Top 40 and the SWIX 40. 3 Mase (2007) makes a similar argument for the FTSE100, and confirms this by demonstrating that for the FTSE100 the index migration price effects are similar for first-time and returning index constituents. Unfortunately there are not yet enough instances of index re-entries on the JSE to make a similar analysis meaningful.…”
Section: Prior Literaturementioning
confidence: 74%
“…2) If so, what are the time-dependent profiles of such CARs (in other words, to what extent does the market discount the probability of an index change in advance)? 3) If CARs are observed, are they permanent, or is this a process that reverses itself within a relatively short period of time post-index additions or deletions?…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal trading volume is generally calculated using the log-transformed percentage of shares outstanding for each security as compared with an estimated market model abnormal trading volume (Ajinkya and Jain, 1989;Cready and Ramanan, 1991;Biktimirov et al, 2004). As with price event studies, both parametric and nonparametric tests are indicated and the same tests utilized for abnormal price returns were used for the abnormal volume returns (Campbell and Wasley, 1996).…”
Section: Additional Statistical Methods Appliedmentioning
confidence: 99%
“…However, they do not find any change in the median number of individual shareholders following deletions. Rigamonti and Barontini (2000), Shu et al (2004) and Biktimirov et al (2004) show that institutional ownership increases following additions to the Mib30, Taiwanese market (MSCI) and Russell 2000 indices, respectively.…”
Section: Related Literaturementioning
confidence: 99%